2017
DOI: 10.1155/2017/7657306
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics Profiling to Identify Biomarkers for Unstable Angina

Abstract: Although statistical evidence is clear regarding the dangerousness of unstable angina (UA), a form of coronary heart disease (CHD) characterised by high mortality and morbidity globally, it is important to recognise that diagnostic precision for the condition is unfavourable. In the present research, to gain insight into candidate biomarkers, the author draws on 1H NMR-based serum metabolic profiling to analyze the unstable angina pectoris (UAP) metabolic signatures; this constitutes an effective way to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Smoking, drinking, hypertension and diabetes are relative to the risk of CVD [2]. Recent studies reported that serum biomarkers such as blood glucose (GLU), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), Uric Acid (UA), thyroid-stimulating hormone (TSH), Homocysteine (Hcy) and other biomarkers were associated with the risk of CVD [2][3][4][5][6][7][8]. However, the results were inconsistent, and most of them focused only on one or several biomarkers, neglected the effect of multi-biomarker for the risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking, drinking, hypertension and diabetes are relative to the risk of CVD [2]. Recent studies reported that serum biomarkers such as blood glucose (GLU), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), Uric Acid (UA), thyroid-stimulating hormone (TSH), Homocysteine (Hcy) and other biomarkers were associated with the risk of CVD [2][3][4][5][6][7][8]. However, the results were inconsistent, and most of them focused only on one or several biomarkers, neglected the effect of multi-biomarker for the risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to cardiovascular disease, Ganna et al analysed the circulating metabolites in patients with coronary heart disease (CHD) and found that four lipid-related metabolites contribute to the development of CHD [8]. Serum metabolomics study revealed that several metabolic markers, including 2-hydroxy, 2-methylpropanoic acid and erythritol, are associated with heart failure [9]. Therefore, metabolomics is an effective and safe approach for the diagnosis, evaluation of severity, and therapy management for diseases in both clinical practice and basic research.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions create a pathological risk of atherosclerosis, as phenotypic changes in the endothelium can lead to dysfunction. Moreover, the development of new drugs and treatments for atherosclerosis requires a more in-depth understanding of the endothelial biology of atherosclerosis [8].…”
Section: Introductionmentioning
confidence: 99%